An analysis on why the mathematics and integrated Natural Sciences basic education teachers diploma (BETD) graduates opted further studies in their areas of specialisation at the Rundu campus, University of Namibia (Journal for Studies in Humanities and Social Sciences, 2017)
This study was conducted to find out why the BETD Mathematics and Integrated Natural Sciences graduates currently studying at Rundu Campus of the University of Namibia (UNAM) opted to further their studies in their areas of specialisation.The profile of the BETD graduates can shed some light on the current training of teachers by the Faculty of Education (FoE) at the Rundu Campus. These graduates were trained in either Upper Primary (UP), grades 5-7 level, or Junior Secondary (JS), grades 8-10 (JS) level, which UNAM did not offer before the merger. Currently the FoE is offering a 4 year Bachelor of Education Honours (B. Ed. Honours) degree at Upper Primary (UP) level, grades 4-7. This enables those who did UP level to articulate in 2nd year, while those who did JS level have to start from year 1, due to the different levels of studies, subject content, skills and methodology acquired. A total number of 26 participants were involved in this research, 11 females and 15 males. The study employed semi-structured interviews, questionnaires, and followed up with stimulated recall interviews to establish their perceptions regarding the reasons why they opted to further their studies at the Rundu Campus, which are mainly as follows: higher level subject con-tent, skills, methodology, distance, finances, accommodation, and work stations that are within the regions.